102k views
22 votes
Find the solution to the following system of equations using substitution or elimination​ y=-2x+7 y=3x-8

User Mihkorz
by
5.2k points

1 Answer

7 votes

Answer:

x = 3, y = 1

Explanation:

By substitution since y = -2x + 7, substitute that for the 2nd y so

-2x +7 = 3x - 8, so x = 3, then substitute the 3 in any of the equations, so y = -2(3) + 7 is equal to 1

If you use elimination you can subtract the two equations from each other to get rid of the y so

y = -2x + 7

-y = -3x + 8

so 0 = -5x + 15, 5x = 15, x=3

User Jcaruso
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.